A fixed‐frequency control method for wireless power transmission battery chargers using a dual‐function compensator - Sina Bajelvand; Amir Babaki; Alireza Jafari‐Natanzi; Ali Yazdian Varjani; Sadegh Vaez‐Zadeh (IET Power Electronics, 2024)
Abstract High efficiency and unity power factor (PF) are the most important requirements of a wireless charger system simultaneous with the output voltage regulation. Achieving all above‐mentioned criteria in a wide range of the load is challenging in the system. This paper presents a novel control approach applied to series‐series wireless power transmission converter by using a dual‐function compensator to achieve unity PF and maximum efficiency during the constant power‐constant voltage (CP‐CV) charging scenarios. A semi‐active rectifier with impedance matching capability along with a switch‐controlled capacitor constitutes the dual‐function compensator on the secondary side. Meanwhile, the primary side inverter executes the CP‐CV charging scenario for the battery with various charging characteristics at a fixed‐switching frequency. Besides that, all secondary side switches experience soft switching condition throughout the battery charging. Finally, a prototype with a power of 200 W and roughly regulated efficiency of 90% is presented in order to verify the proposed control method.